Thermostability of the Recombinant Haemagglutinin-Neuraminidase Glycoproteins of Newcastle Disease Virus - Tang, Yik Kiong (2003)
The haemagglutinin-neuraminidase (HN) glycoprotein of Newcastle disease virus (NDV) is of primary importance in inducing virus-neutralizing antibodies against viral infection in chicken and has been used in the development of many vaccines. A variant strain of the vaccine strain V4QUE known as V4UPM(HR) has been developed as a heat stable vaccine for use in the poultry industry in tropical countries such as Malaysia. This protein may also be involved in maintaining heat stability of some vaccine strains. In this study, the HN gene of the heat stable variant NDV strain V4UPM(HR) and its parental strain V4QUE were cloned and expressed in the Baculovirus Expression Vector System (BEVs) and characterized for their heat stability. The 1.9 kb HN genes of these strains were amplified by RT-PCR from their genomic RNA and unidirectionally cloned into the baculovirus transfer plasmid, peR Bac4.8. These recombinant baculovirus plasmids were then co-transfected with linearized baculoviral DNA, Bac-N-Blue™ DNA into Spodoptera frugiperda (Sf9) insect cell line. The recombinant baculoviruses which were generated as recHNV4UPM(HR) and recHNV4QUE, were purified by plaque assay. The respective recombinant HN glycoproteins (recHNs ) which were expressed in Sf9 insect cells showed haemagglutination (RA) and neuraminidase (NA) activities as well as haemagglutination inhibition (HI) and haem adsorption activities in serological assays. The HA and NA activities were also detected on the surface and in the cytoplasm of the infected Sf9 cells. SDS-PAGE and Western blot analysis of the recombinant baculovirus-infected Sf9 cell lysates detected protein bands of approximately ~74 kDa, which corresponded to the glycosylated HN protein of the virion. These results indicated that the recHNs were not only successfully expressed in the S19 cells but they also appeared to be biologically active and functional.